2011
DOI: 10.1111/j.1365-2893.2010.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of protection against clinical and chronic hepatitis B infection 20 years after infant vaccination in a high endemicity region

Abstract: SummaryVaccination against hepatitis B virus (HBV) immediately after birth prevents neonatal infection by vertical transmission from HBV carrier mothers. There is an ongoing debate whether infant vaccination is sufficient to protect against infection when exposed to HBV later in life. We studied 222 Thai infants born to HBsAg −/+ and HBeAg −/+ mothers who were vaccinated with recombinant hepatitis B vaccine at 0-1-2-12 months of age. A subset of 100 subjects received a booster dose at age 5 years. Blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 20 publications
2
62
1
1
Order By: Relevance
“…antibody levels decay much more rapidly than expected as well as having a historical prevalence on the low-end of the endemic spectrum (3% vs. 6% in Alaska or 9.8% in China) [9,87]. In highrisk regions, antibody levels may remain high in the population due to natural boosting, where constant re-exposure to HBV would lead to persistent antibody production within the host [99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…antibody levels decay much more rapidly than expected as well as having a historical prevalence on the low-end of the endemic spectrum (3% vs. 6% in Alaska or 9.8% in China) [9,87]. In highrisk regions, antibody levels may remain high in the population due to natural boosting, where constant re-exposure to HBV would lead to persistent antibody production within the host [99].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that over time, protective anti-HBs levels begin to decay, and can become undetectable or reduced below the protective threshold (<10 mIU/ml), when initial vaccine dose is given at birth (and followed commonly by second and third dose within the first year of life) [71,91,99]. The decaying antibody levels have called into question whether or not the three dose vaccine is sufficient in protecting the host, or if a booster dose is required [100].…”
Section: Lack Of Need For a Boostermentioning
confidence: 99%
“…10 The anti-HBc-positive rates of the first decade in children of HBeAg-positive mothers were 9.5% and 14.3%, respectively, for whom with and without booster vaccination was at 5 years of age. 11 For their second decade of life, these rates were 22.2% and 28.6%, respectively. 11 More important, HBV DNA was detected with a high frequency (81 of 106) in a cohort of HBsAg(2)/anti-HBs(1)/anti-HBc(1) young adults who were vaccinated neonatally.…”
Section: Replymentioning
confidence: 98%
“…Recent evidence suggests vaccination confers immunity into early adulthood. [35][36][37] This study did not account for infections avoided at later stages in life (eg, during adolescence and adulthood …”
Section: Figurementioning
confidence: 99%